2000
DOI: 10.1210/endo.141.6.7494
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Luteinizing Hormone-Releasing Hormone Neurons Show a Different Migratory Activity in Vitro*

Abstract: The development of two cell lines (GT1 and GN) of immortalized LHRH neurons has allowed an accurate study of the mechanisms controlling the synthesis and the secretion of LHRH. These cell lines, obtained in mice by genetic targeted tumorigenesis, retain many of the phenotypic characteristics of LHRH neurons. Of interest, GT1 cells derive from an hypothalamic tumor, whereas GN cells were obtained from a tumor localized in the olfactory bulb. The different origin of these cell lines lead to hypothesize that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 43 publications
2
28
0
2
Order By: Relevance
“…Previous studies have shown that GN11, but not GT1-7, cells show significant migratory activity and actively respond to the chemotactic stimulus represented by FBS (37).…”
Section: Collagen Gel Assaymentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have shown that GN11, but not GT1-7, cells show significant migratory activity and actively respond to the chemotactic stimulus represented by FBS (37).…”
Section: Collagen Gel Assaymentioning
confidence: 94%
“…This different derivation is indicative of different maturational stages of the two cell lines, as demonstrated by the fact that GT1 cells retain many characteristics of the mature hypothalamic LHRH neurons (34 -36). On the contrary, it has been found recently that GN11 cells retain the phenotypic characteristics of immature LHRH neurons and show high migratory activity in vitro, responding to fetal bovine serum (FBS) as a chemotactic stimulus (36,37).…”
Section: Gn11 Isolated From Tumors Developed In the Hypothalamus Andmentioning
confidence: 99%
See 1 more Smart Citation
“…They not only determine the timing of puberty but ultimately integrate all reproductive inputs (Romanelli et al, 2004;Stevenson et al, 2013). In humans, the GnRHneuronal network is composed of a few hundred neurons distributed as clusters located from the preoptic area to the anterior hypothalamic regions making in vivo or ex vivo experimental studies of GnRH neurons extremely difficult (Maggi et al, 2000;Wang et al, 2015). The molecular ontogeny of GnRH neurons remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work we evaluated the presence of nicotinic receptors and the nature of a direct effect of nicotine on GnRH secretion in a neuronal isolated system using cell lines of immortalized hypothalamic GnRH neurons, an in vitro model widely used to study the mechanisms that control GnRH release in controlled conditions (Glidewell-Kenney et al, 2013;Gore and Roberts, 1997;Krsmanovic et al, 1998;Maggi et al, 2000;Mellon et al, 1990;Pal et al, 2007;Pimpinelli et al, 1999).…”
Section: Introductionmentioning
confidence: 99%